Representations of the Indigenous Peoples Movement in Roraima’s ethnomedia (Intercom - Brazilian Journal of Communication Sciences, 2022)
This research reflects on the ethnomedia practices carried out by the portal of the Indigenous Council of Roraima (CIR), in order to understand how the organization constructs meanings about the Indigenous Peoples Movement. To do so, we characterized the Indigenous Movement and Ethnocommunication; we discussed the relationships between media imperialism and representation through Mattelart (1978); and we used the precepts of Discourse Analysis by Souza (2014) to examine the narratives of the corpus of study, consisting of 89 publications by the CIR in 2018. The results unveil an ethnocommunicative practice that operates on the architecture of discursive representations that have as a principle the circumstance that the natives are original inhabitants of the areas delimited as Indigenous Lands, determining the transmission of this right to their descendants for their continuity as peoples with pre- Columbian ethnic relationships.
Keywords: Ethnocommunication; Ethnomedia; Indigenous Peoples Movement; Amazonian knowledge; Roraima